Synthesis of sericin‐conjugated silver nanoparticles and their potential antimicrobial activity. (1st March 2020) - Muhammad Tahir, Hafiz; Saleem, Fatima; Ali, Shaukat; Ain, Qurat ul; Fazal, Amna; Summer, Muhammad; Mushtaq, Rabia; Tariq Zahid, Muhammad; Liaqat, Iram; Murtaza, Ghulam
Abstract: Nanoparticles (NPs) are being recognized as antibacterial agents due to their rapidly increasing multidrug resistance in bacterial pathogens. Hence, there is an unmet need to identify the natural antibacterial agent. The present study aimed to evaluate the antibacterial activity of sericin‐conjugated silver NPs synthesized by using sericin as a reducing and capping agent. Synthesized NPs were characterized by scanning electron microscope, nanolaser particle size analyzer (BT‐90), Fourier‐transform infrared analysis, and energy‐dispersive X‐ray. The biogenic NPs significantly inhibited the growth of Escherichia coli (12–15 mm zone of inhibition), Staphylococcus aureus (14.6–15.4 mm zone of inhibition), and Klebsiella pneumoniae (12.5–18 mm zone of inhibition). The stability of naturally synthesized NPs was examined at various temperatures (i.e., 4°C, 37°C, and 55°C) and pH (i.e., 3, 7, and 11). Temperature variability did not significantly affect the efficacy of NPs. However, NPs performed better at higher pH levels. This study suggested that the sericin‐based silver NPs are not only effective against bacteria, but they also maintain the stability at different ranges of temperature and pH. We concluded that the sericin‐conjugated silver NPs possess the remarkable antibacterial potential, which suggests their large‐scale use as a cheap and stable antimicrobial agent in the future.